2020
DOI: 10.21203/rs.3.rs-67821/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catastrophic Health Expenditures for Children with Disabilities in Iran: A National Survey

Abstract: Background: Higher health costs and financial burden are imposed on people with disabilities due to their health status associated with their disability. Measuring the incidence of catastrophic health expenditures (CHE) can provide good evidence for health policymakers to assess the current state of financial protection of the health system. The aim of this study was to investigate the percentage of households with disabled children aged 0 to 8 years who had faced CHE due to the health costs of these children … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The difference in the percentage of CHE between provinces was not signi cant.Based on the ndings of this study, in the last year of the sixth ve-year development plan (2017-2021) as a strategic document, like the two previous development plans,Iran not only did not achieve the goal of reducing the percentage of households exposed to CHE to 1% and there is still a big gap to reach that goal, but also, based on the ndings of previous studies, this gap seems to have become deeper [15][16][17]. According to the ndings of another [23]. Also, according to the report of the research center of the Iranian parliament, the value of the CHE index for the country at the end of 2015 (end of the fth development plan) was reported 6% [18].A comparison of the ndings of our study with the ndings of the above studies conducted in recent years shows that the status of the nancial protection index against CHE in Iran not only did not reach the 1% target but rather the gap between the status quo with a predetermined goal and the desired status seems to have widened [15,17,22].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The difference in the percentage of CHE between provinces was not signi cant.Based on the ndings of this study, in the last year of the sixth ve-year development plan (2017-2021) as a strategic document, like the two previous development plans,Iran not only did not achieve the goal of reducing the percentage of households exposed to CHE to 1% and there is still a big gap to reach that goal, but also, based on the ndings of previous studies, this gap seems to have become deeper [15][16][17]. According to the ndings of another [23]. Also, according to the report of the research center of the Iranian parliament, the value of the CHE index for the country at the end of 2015 (end of the fth development plan) was reported 6% [18].A comparison of the ndings of our study with the ndings of the above studies conducted in recent years shows that the status of the nancial protection index against CHE in Iran not only did not reach the 1% target but rather the gap between the status quo with a predetermined goal and the desired status seems to have widened [15,17,22].…”
Section: Discussionmentioning
confidence: 93%
“…The difference in the percentage of CHE between provinces was not signi cant.Based on the ndings of this study, in the last year of the sixth ve-year development plan (2017-2021) as a strategic document, like the two previous development plans,Iran not only did not achieve the goal of reducing the percentage of households exposed to CHE to 1% and there is still a big gap to reach that goal, but also, based on the ndings of previous studies, this gap seems to have become deeper [15][16][17]. According to the ndings of another systematic and meta-analysis study in Iran (2017) conducted by Ghorbaian et al, the prevalence of households faced with CHE was reported to be 3.9% (95% CI, 3.26-11.07) [22].. Also, in the latest systematic and meta-analysis study in Iran (2018) conducted by Aryankhesal et al, in total, the percentage of households exposed to CHE was 7.5% (95% CI, 6.2-9.1) and for inpatient services was 35.9% (95% CI, 23.5-54.3) [15].Based on a national study in Iran (2020) conducted by Moradi et al on households with disabled children, 32.7% of households were exposed to CHE [23]. Also, according to the report of the research center of the Iranian parliament, the value of the CHE index for the country at the end of 2015 (end of the fth development plan) was reported 6% [18].A comparison of the ndings of our study with the ndings of the above studies conducted in recent years shows that the status of the nancial protection index against CHE in Iran not only did not reach the 1% target but rather the gap between the status quo with a predetermined goal and the desired status seems to have widened [15,17,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation